Vehicle routing problem for multiple product types, compartments, and trips with soft time windows - P. Kabcome (2018)
© 2015 P. Kabcome and T. Mouktonglang. This paper presents a mathematical model to solve the vehicle routing problem with soft time windows (VRPSTW) and distribution of products with multiple categories. In addition, we include multiple compartments and trips. Each compartment is dedicated to a single type of product. Each vehicle is allowed to have more than one trip, as long as it corresponds to the maximum distance allowed in a workday. Numerical results show the effectiveness of our model.